2016
DOI: 10.1186/s40792-016-0201-2
|View full text |Cite
|
Sign up to set email alerts
|

Invasive liver abscess syndrome caused by Klebsiella pneumoniae with definite K2 serotyping in Japan: a case report

Abstract: BackgroundKlebsiella pneumonia is a well-known human pathogen, and recently, a distinct invasive syndrome caused by K. pneumoniae serotypes K1 and K2 has been recognized in Southeast Asia. This syndrome is characterized by primary liver abscess and extrahepatic complications resulting from bacteremic dissemination. We report the first adult case of primary liver abscess caused by the definite K2 serotyped pathogen, with endogenous endophthalmitis in Japan.Case presentationA 64-year-old woman was admitted to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 12 publications
(14 reference statements)
2
20
0
Order By: Relevance
“…In a study performed in Taiwan, the serotype K1 was revealed in a higher occurrence rate, 63.4%,that that for the case of K2, 14.2%, of K. pneumonia isolates from liver abscess 23 . In Japan, it has been detected that the rate for the K1 serotype occurrence was lower than that regarding the K2 serotype of K. pneumonia isolates from liver abscesses 24 which shows similar to the current study results. These serotypes were Fig.…”
Section: Discussionsupporting
confidence: 90%
“…In a study performed in Taiwan, the serotype K1 was revealed in a higher occurrence rate, 63.4%,that that for the case of K2, 14.2%, of K. pneumonia isolates from liver abscess 23 . In Japan, it has been detected that the rate for the K1 serotype occurrence was lower than that regarding the K2 serotype of K. pneumonia isolates from liver abscesses 24 which shows similar to the current study results. These serotypes were Fig.…”
Section: Discussionsupporting
confidence: 90%
“…[ 19 ] A publication from Japan in 2016, described K1 serotype in one and K2 serotype in two liver abscess patients. [ 20 ] The presence of K1 or K2 serotypes are also being reported from North America, Europe, Australia, Africa, and the Middle East. [ 6 ] Although K1/K2 serotypes are frequently associated with liver abscess, they have been isolated from extrahepatic abscess also.…”
Section: Discussionmentioning
confidence: 99%
“…The syndrome of metastatic infections from hv K. pneumoniae infections, to a large extent, has been restricted geographically in Asia. Although a few established reports in North America and Europe were documented, interestingly majority of cases have occurred disproportionately in persons of Asian descent 1–10. The hv strains, especially K1 and K2 capsular serotypes, are highly associated with a wide range of highly complicated and invasive diseases,8–10 including soft tissue infections such as necrotising fasciitis 1…”
Section: Discussionmentioning
confidence: 99%
“…Its incidence is less common than exogenous endophthalmitis, which commonly results from trauma or cataract surgery. Primary liver abscesses are the most common primary site, accounting for metastatic spread with an approximate risk as high as 11% of developing endophthalmitis vs 4.8% in patients with bacteraemia 7 8. Bilateral involvement occurs in 13%–25% 10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation